2020
DOI: 10.3324/haematol.2020.266593
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: risk of infection is high, independently of ABO blood group

Abstract: ing cell lines by conditional gene tagging reveals rapid HIF-2 driven Epo kinetics, cell autonomous feedback regulation, and a telocyte phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…The present study findings are in line with the studies carried in France (patients with blood type O required more O2 and ICU) [17,18], Canada (patients with blood type O were less infected with a severe illness) [20], Turkey (patients with blood type O were less infected and those with blood type A less associated with mortality) [22], Spain [16], China [24], Denmark [27], Sudan [30], and Iran [31] and the metanalysis carried out by [32] (patients with blood type O were less infected).…”
Section: Discussionsupporting
confidence: 93%
“…The present study findings are in line with the studies carried in France (patients with blood type O required more O2 and ICU) [17,18], Canada (patients with blood type O were less infected with a severe illness) [20], Turkey (patients with blood type O were less infected and those with blood type A less associated with mortality) [22], Spain [16], China [24], Denmark [27], Sudan [30], and Iran [31] and the metanalysis carried out by [32] (patients with blood type O were less infected).…”
Section: Discussionsupporting
confidence: 93%
“…More recent studies on SARS-CoV-2 reported similar associations between viral infection and the ABO blood groups (15,16). However, divergent results are still coming forth with respect to the role of the ABO blood groups as a risk marker for COVID-19 severity linked to possible comorbidities and methodological differences as well as population differences in tissue receptors associated with SARS-CoV-2 infection (4,13,(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…The changes in host susceptibility to many infections are actually because of diversities in blood group antigen expression (Cooling, 2015 ). That is why more and more researches found out that the O blood type is a protection factor against COVID-19 infection and severe COVID-19 illness (Flegel, 2020 ; Wu et al, 2020 ; Liu et al, 2021 ; Ray et al, 2021 ), whereas a study reported that the interactions of the ABO and secretor types in the cohort of patients compared with the blood donors lack significant differences, so they suggested that that emphasis should not be put on the ABO antigenic structures, but rather on the isoagglutinin (Matzhold et al, 2021 ). In addition to using different antigens, different ABO blood groups also contain different situations of isoagglutininsin.…”
Section: Discussionmentioning
confidence: 99%
“…The Le (a–b–) type appeared to be at least a mitigating factor against hospitalization with COVID-19. Invariably, many study results reach a consensus that the O blood type acts as a protection factor against COVID-19, while no ABO blood group type can protect an individual from becoming infected (Flegel, 2020 ). Notably, individuals able to express these antigens on epithelial cells, known as the FUT2 gene secretion status, indicated a higher degree of exposure to SARS-CoV-2 (Shokri et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%